The correlation of international trade and growth in Indonesia - Barianto Nurasri Sudarmawan (Jurnal Ekonomi dan Pembangunan, 2022)
Exports generate foreign exchange that can be used for economic activities. On the other hand, imports also give households and companies more choices in consuming goods. In other words, international trade provides advantages for each country. There have been many studies that attempt to empirically prove the relationship between export-import and economic growth. The aim of this study is to re-examine the relationship between exports, imports, and growth in the short run and long run in Indonesia. This study employed the Granger Causality test and VECM to find long-term and short-term respectively. This research used secondary data annually from 1980 to 2019. Result of this empirical study, we find correlating variables are GDP-Exports, GDP-Imports, and Imports-Exports in the long-term. These three long-term findings match the short-term findings explained by VECM modeling. According to these findings, the policy recommendation is Indonesia needs to import carefully because importing consumption goods is a sure way to deplete its own foreign exchange reserves. Second, based on our empirical found, importing intermediate goods can increase our export, so we suggest Indonesia should run substitution import strategy immediately